Antimicrobial Effect of Ethanol Extract of Red Betel Leaf (Piper crocatum) on the Growth of Klebsiella pneumoniae bacteria - Wielim, Edbert; ., Marwoto; Afifah, Zulaika Nur (Nexus Biomedika, 2017)
Background:Red betel leaf (Piper crocatum) as a herbal plant has been exist through generations, and can be trusted to heal many diseases such as diabetes mellitus, cancer, and hemoroid. According to the research, red betel leaf has some compounds that can be used as antibiotics for example like, flavonoid, alkaloid, tanin, and essential oil. Klebsiella pneumoniae is one cause of nosocomial infection, which Klebsiella pneumoniae has been resistant to certain antibiotics known as Extended Spectrum b Lactamase (ESBL). The purpose of this research is to know the effect of Ethanol extract red betel the Growth of Klebsiella pneumoniae. Methods: This research was an laboratory experimental with post test only with contro group design, conducted in Microbiology Laboratory Faculty of Medicine of Sebelas Maret University, Surakarta. The sample were ATCC standard of Klebsilla pneumonia, clinics isolate of ESBL, and clinics isolate of non ESBL. ESBL and biochemical test were attempted first. After ESBL were proven, the next step was preliminary test and according to preliminary test, 70% ethanol extract of red betel leaf was used for this research. Negative control was ethanol 70%, positive control was cefoperazone+sulbactam, and treatment group was 70% ethanol extract of red beter leaf. Kruskal Wallis and Mann Whitney were used for analyse the data in this research. Results: According to the research, there was no inhibiton zone that formed on negative control, ethanol extract 70% of clinics isolate of non ESBL, and clinics isolate of ESBL. Inhibition zone formed on ethanol extract 70% of ATCC (10,3 ± 0,57 mm), positive control of ATCC (37,5 ± 1,15 mm), positive control of clinics isolate of non ESBL (36,1 ± 5,63 mm), and positive control of clinics isolate of ESBL (23,9 ± 1,19 mm). Kruskal Wallis showed there was statistically significant difference to all the sample (p= 0,000). Mann Whitney showed there was statistically difference between ethanol extract 70% of ATCC with clinics isolate of ESBL and clinics isolate of non ESBL (p=0,01), positive control of clicnis isolate of ESBL with ATCC (p= 0,219), and ethanol extract 70% of ATCC with positive control of ATCC (p =0,043). Conclusion : There was a different between the growth of all the sample of Klebsiella pneumoniae. Keywords:ethanol extract of red betel leaf, Klebsiella pneumoniae.